Damned whores or founding mothers? Representations of convict women in Australian literature - DOI: 10.4025/actascilangcult.v32i1.5713 - Lou Drofenik (Acta Scientiarum. Language and Culture, 2009)
When writing about European settlement in Australia, nineteenth and early twentieth century writers focused on the lives of the male convicts and on the English middle class who were in charge of the colony. It was only in the latter part of the twentieth century that Australian feminist writers started to take an interest in the lives of women convicts. Working from different theoretical perspectives, feminist writers patiently unraveled the lives of convict women hidden within layers of archival material. Thus started the debate of whether convict women should be regarded as Damned Whores or Founding Mothers. Were these women all prostitutes transported for their vices? Or were they women, who struggling for survival in their native land were transported for trivial crimes in order to populate a country which had long been settled by Aboriginal nations? Were these women Founding Mothers who left a legacy not only of Australian born children but also of values embedded in Australian culture? How does Australian literature represent these women? This essay deals with female convicts transported to Australia from Great Britain and Ireland. In this essay I will look at the way writers have depicted their lives and I will examine the way their narratives helped to shape the culture in which they lived and if their legacy lives in today’s Australia.